Running overload - Miller, Connie Colwell, 1976-; Francisco, Tina (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2020)
Eighth-grader Somali American Nimo Mohamed is the youngest runner on the varsity cross-country team, but she is determined to keep up with the older girls, so she has set herself a grueling training schedule; too grueling because her body is exhausted, her grades at school are slipping, and her father, who is still very much in her life despite the divorce, is starting to pressure her to quit the team.
3.6
3-6
GN540L
Keywords: Cross-country running -- Comic books, strips, etc. -- Juvenile fiction; Somali Americans -- Comic books, strips, etc. -- Juvenile fiction; Fathers and daughters -- Comic books, strips, etc. -- Juvenile fiction; Running -- Fiction; Somali Americans -- Fiction; Fathers and daughters -- Fiction; Divorce -- Fiction; Cartoons and comics; Sports comics; Graphic novels; Comics (Graphic works)